Analysis and Experimental Demonstration of Reflectarray Antennas in Quasi-Regular Lattices - Borja Imaz-Lueje; Juan Corcoles; Marcos R. Pino; Manuel Arrebola (IEEE Open Journal of Antennas and Propagation)
This paper presents investigations on reflectarray antennas using non-periodic element distributions. The study involves the analysis and design of two reflectarrays based on quasi-periodic lattices with rectangular and pentagonal profiles, whose performance is compared with equivalent reflectarrays comprised of regular grids of elements. The characterization of these antennas is performed using a tailored analysis technique for reflectarrays with periodical and quasi-periodical grids. The proposed technique uses the Method of Moments under local periodicity conditions (MoM-LP) to compute the field on the surface of each cell and then the far field radiated by the aperture. In both aperture profiles, the quasi-periodic lattices are designed to provide an optimal adjustment, with the edge of the reflectarray maintaining an inter-element spacing similar to the regular grids of elements. This is particularly useful in non-canonical profile apertures, where the regular lattices do not adjust properly with the shape of the reflectarray and therefore exhibit less control of the reflected field in the aperture. The reflectarrays comprised of quasi-regular lattices achieve similar performance in terms of beam shaping, SLL and crosspolar discrimination to those based on regular grids. However, they show an improvement in fractional bandwidth between 7.4% and 11.3%.